The untouchables - De Palma, Brian; Linson, Art.; Mamet, David; Costner, Kevin; Smith, Charles Martin; Garcia, Andy.; De Niro, Robert; Connery, Sean.; Burum, Stephen H., 1939-; Morricone, Ennio; Ness, Eliot; Paramount Pictures Corporation (Hollywood, Calif. : Paramount, 2004)
A larger-than-life depiction of Al Capone, the warlord who ruled Prohibition-era Chicago ... and Eliot Ness, the law enforcer who vowed to bring him down. In this classic confrontation between good and evil, Ness learns, with the help of a cop named Malone, how to beat the mob by shooting fast and shooting first.
Originally produced as a motion picture in 1987.
Based on the novel by Eliot Ness.
Special features: The script, the cast; Production stories; Reinventing the genre; The classic; Original featurette: "The men"; Theatrical trailer.
Director of photography, Stephen H. Burum ; art director, William A. Elliott ; editors, Jerry Greenberg and Bill Pankow ; music, Ennio Morricone ; costume designer, Marilyn Vance-Straker ; wardrobe, Giorgio Armani.
Kevin Costner, Charles Martin Smith, Andy Garcia, Robert De Niro, Sean Connery.
MPAA rating: R ; special features not rated.
Keywords: Ness, Eliot -- Drama; Capone, Al, -- 1899-1947 -- Drama; Capone, Al, -- 1899-1947.; Ness, Eliot; Ness, Eliot -- Drama; Gangsters -- Illinois -- Chicago -- Drama; Prohibition -- Illinois -- Chicago -- Drama; Criminal investigation -- Illinois -- Chicago -- Drama; Criminal investigation; Gangsters; Prohibition; Gangsters -- Drama; Illinois -- Chicago; Crime films; Drama; Feature films; Gangster films; Video recordings for the hearing impaired; Gangster films; Crime films; Feature films; Video recordings for the hearing impaired; Gangster -- Feature; Crime -- Feature; Gangster -- Feature; Crime -- Feature